2011
DOI: 10.3389/fnint.2011.00054
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making in the ventral premotor cortex harbinger of action

Abstract: Although the premotor (PM) cortex was once viewed as the substrate of pure motor functions, soon it was realized that it was involved in higher brain functions. By this it is meant that the PM cortex functions would better be explained as motor set, preparation for limb movement, or sensory guidance of movement rather than solely by a fixed link to motor performance. These findings, together with a better knowledge of the PM cortex histology and hodology in human and non-human primates prompted quantitative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 134 publications
(286 reference statements)
1
9
0
Order By: Relevance
“…This notion corresponds with other recent reports that suggest that the posterior DLPFC and premotor structures are involved in transforming sensation into action, i.e. the use of sensory information in a complete cascade of decision making, execution and evaluation of the outcome of the decision [Acuña et al, ; Heekeren et al, ; Pardo‐Vazquez et al, , ; Romo et al, ]. Whether or not the relatively large groups of electrodes assigned to both the PreCG/MFG1 (ROI4) and PreCG/MFG2 (ROI16) can be further distributed into separate subfunctions remains to be determined.…”
Section: Discussionsupporting
confidence: 87%
“…This notion corresponds with other recent reports that suggest that the posterior DLPFC and premotor structures are involved in transforming sensation into action, i.e. the use of sensory information in a complete cascade of decision making, execution and evaluation of the outcome of the decision [Acuña et al, ; Heekeren et al, ; Pardo‐Vazquez et al, , ; Romo et al, ]. Whether or not the relatively large groups of electrodes assigned to both the PreCG/MFG1 (ROI4) and PreCG/MFG2 (ROI16) can be further distributed into separate subfunctions remains to be determined.…”
Section: Discussionsupporting
confidence: 87%
“…Whereas, ventral premotor area (PMv) an anatomical and physiological well differentiated area in premotor cortex supports both perceptual decisions and performance monitoring. A study suggested that PMv is involved in the use of recent and long term sensory memory to decide, execute and evaluate the outcomes of the subjects' choices (Pardo-Vazquez et al 2011).…”
Section: Possible Neural Mechanismmentioning
confidence: 99%
“…In addition, the right preCG and MFG included in the left SII seed connective network was probably the premotor cortex. This region was associated with the whole perceptual decision processing, including maintaining the first stimuli in working memory, with comparison between the two stimuli and motor commands expressing the result of the comparison (for review see Pardo-Vazquez et al, 2011 ). Therefore, we suggest that the psychophysiological interaction of left SII, left SI and right preCG was more correlated to the tactile angle perception and comparison process.…”
Section: Discussionmentioning
confidence: 99%